Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Majlis Menandatangai Memorandum Persefahaman UMP Heitech - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
As of now, we have a number of 9 faculties specialising in engineering and technology, 6 Centres of Excellence, 707 academic staff with 57% of them, 406, are PhD holders, and almost 400 Intellectual Properties including patents. The significant increase of PhD holders and Intellectual Properties at UMP these past few years indicate our commitment in providing the best talent and resources to work not only with our students but also industries.